2010
DOI: 10.1007/s00122-010-1296-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding QTL increases seedling resistance to crown rot (Fusarium pseudograminearum) of wheat (Triticum aestivum)

Abstract: Crown rot of wheat (Triticum aestivum), predominantly caused by the fungus Fusarium pseudograminearum, has become an increasingly important disease constraint in many winter cereal production regions in Australia. Our group has previously identified a range of quantitative trait loci (QTL) for partial resistance to crown rot in various bread wheat sources. Here we report on work that has assessed the effectiveness of pyramiding QTL to improve resistance to crown rot. Two doubled haploid populations were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
(38 reference statements)
3
51
3
2
Order By: Relevance
“…A QTL at a similar location was found to be the sole QTL responsible for the resistance from the genotype Ernie . A QTL on 3B was also the most significant among those detected in the resistant genotype 'W21MMT70' (Bovill et al 2010). However, the 3B QTL in this third resistant genotype was not detected in a different population where the same resistant genotype was involved (Bovill et al 2006) and it is likely that the expression of the QTL from 'W21MMT70' is a product of a specific interaction.…”
Section: Introductionmentioning
confidence: 82%
“…A QTL at a similar location was found to be the sole QTL responsible for the resistance from the genotype Ernie . A QTL on 3B was also the most significant among those detected in the resistant genotype 'W21MMT70' (Bovill et al 2010). However, the 3B QTL in this third resistant genotype was not detected in a different population where the same resistant genotype was involved (Bovill et al 2006) and it is likely that the expression of the QTL from 'W21MMT70' is a product of a specific interaction.…”
Section: Introductionmentioning
confidence: 82%
“…Rating of crown rot disease using seedling leaf sheath tissues has become widely used due to its rapid nature and the ability to grow large quantities of seedlings in controlled growth environments (Wildermuth and McNamara 1994;Mitter et al 2006;Li et al 2008). While these assays have been reported to correlate with ratings performed on adult plants in the field, they cannot replace field grown trials, particularly since some adult plant resistances have been demonstrated (Wildermuth et al 2001;Wallwork et al 2004;Bovill et al 2010). …”
Section: Introductionmentioning
confidence: 98%
“…They were found on five different chromosomes. However, recent studies have identified a major QTL on the long arm of chromosome 3B for CR resistance in three different wheat genotypes (Li et al, 2010a;Ma et al, 2010, Bovill et al, 2010. The magnitude of the 3B CR QTL identified in these genotypes explained up to 34.6%, 40.2%, and 46.2% of the phenotypic variance with detection in each of the trials in the three independent studies.…”
Section: Introductionmentioning
confidence: 93%
“…Fortunately, recent studies have identified a major QTL on the long arm of chromosome 3B conferring CR resistance in three different wheat genotypes, two of them belong to T. aestivum (Li et al, 2010a;Bovill et al, 2010), another belong to T. spelta (Ma et al, 2010). The magnitude of the 3B CR QTL identified in the wheat genotypes 'Ernie' and 'CSCR6' explained up to 34.6% and 46.2% of the phenotypic variance with detection in each of the trials with the use of two different F. pseudograminearum and F. graminearum isolates.…”
Section: Validation Of 3h Qtlmentioning
confidence: 99%
See 1 more Smart Citation